GENDERED FEDERALISM: ISSUES AND CHALLENGES TO WOMEN’S POLITICAL PARTICIPATION IN SINDH, PAKISTAN - Dr Jalil Ahmed; Maqsood, Dr Naila; Dr. Sumaira Nawaz (Journal of Arts & Social Sciences, 2021)
This research article will examine the challenges and prospects of women participating in the politics of Sindh. Generally, in Pakistan the women are always suppressed and they are neglected in policy making process and the political system of Pakistan mainly dominated by the male and the subject of policy making is considered as the subject of of the male. Despite this, women have been active in the politics of Sindh from the time of the Pakistan movement. Benazir Bhutto also hailed from Sindh and became Prime minister of Pakistan twice once in 1988 and then in 1993. However, the women in Sindh have a very limited role in the politics of the Province. The research aims to analyze various Ideological, socioeconomic, political, and psychological constraints and the challenges the women face in Sindh. The paper mainly emphasizes the role of Sindhi society, centuries-old traditions, predetermined gendered roles- patriarchy and male dominancy in social and political institutions, and religious misperceptions that barricade women’s political representation in the province.